Studies in the Urartian Bronze Objects from Japanese Collections (1) - Tanabe, Katsumi
Introduction (p. 1-2) by K. Tanabe; Bibliography of Urartian Studies before 1982 (p. 3-67) by T. Hayashi; Catalogue (p. 68-76) by A. Hori, S. Miyashita and K. Ishida.